Odontogenic differentiation of dental pulp-derived stem cells on tricalcium phosphate scaffolds - Mohamadreza Baghaban Eslaminejad; Sima Bordbar; Hamid Nazarian (Elsevier, 2013)
Background/purpose: The regeneration of dental-related tissue is a major problem in dentistry. Thus, it is beneficial to develop dental constructs that are fabricated with dental pulp stem cells (DPSCs) and an appropriate scaffold. The present study investigates the level of odontogenic differentiation of human DPSCs on tricalcium phosphate (TCP) scaffolds. Materials and methods: We isolated pulp stem cells from human third molars and culture-expanded them through several successive subcultures. The cells from passage 3 were then loaded onto TCP scaffolds and treated with odontogenic supplements (OSs) that included vitamin D3 for a period of 21 days. DPSCs cultivated on TCP without OS, a monolayer culture treated with OS, and normal pulp tissue were the controls. We compared the groups in terms of odontogenic differentiation markers. Results: Alkaline phosphatase (ALP) activity and the amount of culture mineralization, as well as the expression levels of dentin sialophosphoprotein (DSPP) and dentin matrix acidic phosphoprotein 1 (DMP1) genes tended to be significantly higher in the three-dimensional (3D) cultures treated with OS compared to those 3D cultures without OS and the monolayer culture with OS (P < 0.05). The differentiation level in 3D cultures was considerably lower than that in pulp tissue extracted from third molars (P < 0.05). 3D culture on TCP without OS showed a level of differentiation indicating an odontogenic property of the TCP biomaterial. Conclusion: The 3D culture system improves odontogenic differentiation of DPSCs. The differentiation level of the cells in 3D culture is significantly lower than that of odontoblasts present in pulp tissue. TCP biomaterial possesses an odontogenic-inducing property.